Isolasi dan Identifikasi Bakteri Asam Laktat Indigenous dari Sawi Asin - NiMade IndriHapsari Arihantana (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
“Sawi asin” (fermented vegetable) is a fermented product of vegetables which occur naturally (indigenous). Sawi asin has a longer shelf life then fresh or raw vegetables; due to a certain lactic acid bacteria (LAB) presence in sawi asin which produces bacteriocin which destroy bacteria that causes food to spoil. The research was carried out to isolate and identify LAB species in sawi asin (sawi asin produced by MS, Malang; sawi asin produced by Niki Echo Surabaya and sawi asin produced by Wahana Boga Malang, East Java). The LAB characteristics such as cell morphology, Gram staining, motility, catalase, and gas production from glucose were observed. Identification of LAB species was carried out by using kit equipment (sets) API 50 CH and API 50 CHL medium version 5.1 continued by data analysis using APIWEB software. Result of research obtained were 21 LAB isolates (indigenous). The kit set used suceeded in identifying one LAB species, Lactobacillus fermentum 1 with five strains: L. fermentum I SAA1, L. fermentum I SAA2, L. fermentum I SAA4, L. fermentum I SAB1, and L. fermentum I SAC1.